Price-Dependent Profit Sharing as a Channel Coordination Device - Foros, Øystein; Hagen, Kåre P.; Kind, Hans Jarle (Management Science, 2009)
We show how an upstream firm, by using a price-dependent profit-sharing rule, can prevent destructive competition between downstream firms that produce relatively close substitutes. With this rule, the upstream firm induces the retailers to behave as if demand has become less price elastic. As a result, competing downstream firms will maximize aggregate total channel profit. When downstream firms are better informed about demand conditions than the upstream firm, the same outcome cannot be achieved by vertical restraints such as resale price maintenance. Price-dependent profit sharing may also ensure that the downstream firms undertake efficient market expanding investments. The model is consistent with observations from the market for content commodities distributed by mobile networks.